Fräulein von Orleans - Cruz, Benilton Lobato (Revista de Letras, 2016)
The following paper “Fräulein von Orleans “ analyzes and proves the presence of Friedrich Schiller, from the play The Maiden of Orleans, 1881, the character Elza, from the novel by Mario de Andrade, “Amar, verbo intransitivo” . The pedagogical action of the governess, hired to teach piano and German to children in a mansion in Higianópolis, São Paulo, is who believes in art as a form of education, shaped by moral values , however, in conflict with the bourgeois behavior paulistanos new rich. This “Joana D’Arc “ is not sacrificed to the fire, but she is “ dead “ in combat, sacrificed as a typical romantic heroine, as the work of German playwright, in attempting to balance objectivity and subjectivity, by this time, in the unstable bourgeois world, in São Paulo. There is a Elza that goes beyond the sexual initiation of the future Sousa Costa, there is a Fräulein von Orleans, a “universal “ German - French, like a “ mother of love”, which can not fail to appear without their “ flag” of morality.